Pengaruh Variasi Temperatur dan Promotor Zn terhadap Konversi Karbon Dioksida (CO2) Menggunakan Katalis Ni/Al2O3 - Novariana, Mayra; Junaidi, Robert; Mujiyanti, Apri (Jurnal Teknologi, 2025)
The ever-increasing need for fossil fuels, including natural gas, petroleum, and coal, to drive economic growth, has triggered a significant increase in carbon dioxide emissions. Methane is the most basic hydrocarbon compound, under standard temperature and pressure conditions, methane is a colorless and odorless gas. Nickel-based catalysts are the most widely used catalysts in the CO₂ methanation process because they have high activity and selectivity towards methane (CH₄) formation. This study aims to optimize the conversion of carbon dioxide into methane gas using a Catalytic Batch Reactor with the help of a Ni/Al₂O₃ catalyst with variations in temperature and NaOH flow rate. In this study, CO₂ is used as a raw material with a Ni/Al₂O₃ catalyst and a Zn promoter. The Zn Promoter Mass and temperature will be regulated with variations. For methane gas analysis, a Multi Gas Detector Analyzer will be used. From this study, the results showed that the highest methane gas (CH₄) was obtained at a temperature of 200°C with the addition of 15 grams of Zn promoter, which is 56.44%.